2021
DOI: 10.1002/jbm4.10456
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Reduces COMPopathy in Mice Through Activation of Autophagy

Abstract: Misfolding mutations in cartilage oligomeric matrix protein (COMP) cause it to be retained within the endoplasmic reticulum (ER) of chondrocytes, stimulating a multitude of damaging cellular responses including ER stress, inflammation, and oxidative stress, which ultimately culminates in the death of growth plate chondrocytes and pseudoachondroplasia (PSACH). Previously, we demonstrated that an antioxidant, resveratrol, substantially reduces the intracellular accumulation of mutant-COMP, dampens cellular stres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 68 publications
(189 reference statements)
1
38
0
Order By: Relevance
“…Protecting chondrocytes from stress is a central mission in the PSACH treatments. Administration of resveratrol in PSACH patients at an early age (approximately 2 years after birth) may be a promising treatment that activates autophagy and clears mutant-COMP retention [ 138 ]. Anti-inflammation and anti-MMPs reagents may also be important options to reduce the catabolism effects in the PSACH cartilage.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Protecting chondrocytes from stress is a central mission in the PSACH treatments. Administration of resveratrol in PSACH patients at an early age (approximately 2 years after birth) may be a promising treatment that activates autophagy and clears mutant-COMP retention [ 138 ]. Anti-inflammation and anti-MMPs reagents may also be important options to reduce the catabolism effects in the PSACH cartilage.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…For example, resveratrol has neuroprotective properties against various neurological disorders [ 63 ] through the activation of the AMPK autophagy signaling pathway [ 64 ]. Resveratrol could reduce mTORC1 signaling for the activation of autophagy [ 65 ]. In addition, resveratrol can induce autophagy in embryonic stem cells by activating the AMPK pathway and the concomitant suppression of the mTORC1 signaling cascade [ 66 ].…”
Section: Beneficial Components From Natural Products For the Treatmen...mentioning
confidence: 99%
“…Previously, we have shown that resveratrol treatment reduces ER stress by promoting autophagy that clears accumulated mutant-COMP from the ER in growth plate chondrocytes of MT-COMP mice [75]. Resveratrol relieved the ER protein accumulation and reduced chondrocyte death, restoring proliferation and supporting limb growth in juvenile MT-COMP mice [75]. Based on these results, resveratrol was administered to determine whether it could prevent and/or reduce joint degeneration in MT-COMP mice.…”
Section: Prevention Of Joint Degeneration In Mt-comp Mice With Resveratrol Treatment or Ablation Of Chopmentioning
confidence: 99%